Reactive Oxygen Species as Intracellular Signaling Molecules in the Cardiovascular System - Krylatov, Andrey V. (Curr Cardiol Rev, 2018)
BACKGROUND: Redox signaling plays an important role in the lives of cells. This signaling not only becomes apparent in pathologies but is also thought to be involved in maintaining physiolog-ical homeostasis. Reactive Oxygen Species (ROS) can activate protein kinases: CaMKII, PKG, PKA, ERK, PI3K, Akt, PKC, PDK, JNK, p38. It is unclear whether it is a direct interaction of ROS with these kinases or whether their activation is a consequence of inhibition of phosphatases. ROS have a biphasic effect on the transport of Ca2+ in the cell: on one hand, they activate the sarcoplasmic reticu-lum Ca2+-ATPase, which can reduce the level of Ca2+ in the cell, and on the other hand, they can inac-tivate Ca2+-ATPase of the plasma membrane and open the cation channels TRPM2, which promote Ca2+-loading and subsequent apoptosis. ROS inhibit the enzyme PHD2, which leads to the stabiliza-tion of HIF-α and the formation of the active transcription factor HIF. CONCLUSION: Activation of STAT3 and STAT5, induced by cytokines or growth factors, may include activation of NADPH oxidase and enhancement of ROS production. Normal physiological produc-tion of ROS under the action of cytokines activates the JAK/STAT while excessive ROS production leads to their inhibition. ROS cause the activation of the transcription factor NF-κB. Physiological levels of ROS control cell proliferation and angiogenesis. ROS signaling is also involved in beneficial adaptations to survive ischemia and hypoxia, while further increases in ROS can trigger programmed cell death by the mechanism of apoptosis or autophagy. ROS formation in the myocardium can be re-duced by moderate exercise